Modeling the functional influence of vegetation type on streambank cohesion. Issue 9 (21st April 2014) - Polvi, Lina E.; Wohl, Ellen; Merritt, David M.
ABSTRACT The important role of vegetation in adding cohesion and stabilizing streambanks has been widely recognized in several aspects of fluvial geomorphology, including stream restoration and studies of long‐term channel change. Changes in planform between braided, meandering, and anabranching forms have been attributed to the impacts of vegetation on hydraulic roughness and bank stability. However, these studies focus either on flume studies where analog vegetation is used, or case studies featuring one species, which is commonly invasive. We present functional differences of bank‐stabilizing root characteristics and added cohesion, with vegetation categorized as woody and non‐woody and by the vegetation groups of trees, shrubs, graminoids, and forbs. We analyzed root morphology and tensile strength of 14 species common to riparian areas in the southern Rocky Mountains, in field sites along streambanks in the montane and subalpine zones of the Colorado Front Range. Using the vegetation root component (RipRoot) of a physically‐based bank stability model (BSTEM), we estimated the added cohesion for various sediment textures with the addition of each of the 14 species. Significant differences exist between woody and non‐woody vegetation and between the four vegetation categories with respect to the coefficient of the root tensile strength curve, lateral root extent, and maximum root diameter. Woody vegetation (trees and shrubs) have higher values of all three parameters than non‐woody species. Tree roots add significantly more cohesion to streambanks than forb roots. Additionally, rhizomes may play an important role in determining the reach‐scale effects of roots on bank stabilization. Differences in root characteristics and added cohesion among vegetation categories have several important implications, including determining the likelihood of planform change, developing guidelines for the use of bank‐stabilizing vegetation, and linking the effect of vegetation to geomorphic structure that can benefit ecosystem functioning. Copyright © 2014 John Wiley & Sons, Ltd.